2019
DOI: 10.1523/jneurosci.1460-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Gates a Voltage-Dependent Cation Current inAplysiaNeuroendocrine Cells

Abstract: Nonselective cation channels promote persistent spiking in many neurons from a diversity of animals. In the hermaphroditic marinesnail, Aplysia californica, synaptic input to the neuroendocrine bag cell neurons triggers various cation channels, causing an ϳ30 min afterdischarge of action potentials and the secretion of egg-laying hormone. During the afterdischarge, protein kinase C is also activated, which in turn elevates hydrogen peroxide (H 2 O 2), likely by stimulating nicotinamide adenine dinucleotide pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 127 publications
4
11
0
Order By: Relevance
“…In keeping with gating a cation current, H 2 O 2 elicited prolonged action potential firing from whole‐cell current‐clamped cultured bag cell neurons bathed in nASW with K + ‐Asp‐based intracellular saline, that is, physiological conditions. We verified our past report (Chauhan & Magoski, 2019) that bath‐application of 1 mM H 2 O 2 to a neuron set to a resting potential of −40 mV, the average membrane potential during the afterdischarge, caused an ∼9 mV depolarization and consistently generated an afterdischarge‐like burst of spikes ( n = 10) (Fig. 1 and ).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…In keeping with gating a cation current, H 2 O 2 elicited prolonged action potential firing from whole‐cell current‐clamped cultured bag cell neurons bathed in nASW with K + ‐Asp‐based intracellular saline, that is, physiological conditions. We verified our past report (Chauhan & Magoski, 2019) that bath‐application of 1 mM H 2 O 2 to a neuron set to a resting potential of −40 mV, the average membrane potential during the afterdischarge, caused an ∼9 mV depolarization and consistently generated an afterdischarge‐like burst of spikes ( n = 10) (Fig. 1 and ).…”
Section: Resultssupporting
confidence: 88%
“…In addition, we demonstrated that OAG enhances the activity of a different, voltage‐ dependent cation channel in cell‐free patches (Sturgeon & Magoski, 2018). Our prior work also indicates that the H 2 O 2 ‐induced macroscopic current is biophysically and pharmacologically the same as the voltage‐dependent cation conductance observed at the single‐channel level (Chauhan & Magoski, 2019). Thus, we tested whether the H 2 O 2 ‐induced cation current is similarly augmented by phosphoinositide metabolites in cultured bag cell neurons.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations